Hanging by a promise the hidden God in the theology of Oswald Bayer - Miller, Joshua C. (Pickwick Publ., 2015)
Oswald Bayer is one of the most important contemporary interpreters of Martin Luther and confessional Lutheran theologians. As a Luther scholar, Bayer has identified the precise reformational turning point in Luther's life and theology, which is also the central point for a truly Lutheran theology: the promise of a forgiving and justifying God preached in Jesus Christ. As a Lutheran theologian, Bayer stresses that this promise of God is the ultimate subject matter of all theology, and that all other theological topics have the justifying promise of God as their basis and boundary. Hanging by a Promise investigates how Bayer addresses Luther's topic of the hidden God--a God of wrath who accomplishes everything--from the standpoint of the justifying promise of God. Luther's doctrine of the hidden God has been taken up, discussed, and interpreted by many in the modern Protestant theological tradition. Yet, Bayer addresses it in a way in which others before him have not. Going beyond interpretation and evaluation, Bayer actually makes use of Luther's hidden God in his own theology. For Bayer, the hidden God is the counterpoint to God's gracious promise given in the preached Christ, a counterpoint that brings serious tension into the very heart of theology